The voyages and colonising enterprises of Sir Humphrey Gilbert. - Quinn, David B. (Works issued by the Hakluyt Society ;, 2010)
A collection of documents, chiefly from English sources, including a few relating to Ireland, edited with introduction and notes. The main pagination of this and the following volume (Second Series 84) is continuous. This is a new print-on-demand hardback edition of the volume first published in 1940.